(3GdYeGd h GdJMhdGJ GdGbJUGOjI h GdSjGSjI h GdGLJeGYjI(B. /s - (3YdGe, GYJeGO eMeOs ((3GdbGgQI(B: s (3eQcR OQGSGJ h HMhK GdOhd GdfGejI(B, s, 2004)
(3GJLGgGJ GdJTZjd h GdGLhQ aj GdeTQhYGJ GdUZjQI h OQGSI JMdjdjI dGhVGY GdHWGdI h GdJTZjd aj eUQ h cPG efXeI GdYed GdOhdjI h MeGjI GdYeGd(B, (3GVGaI Gdi GHYGO h GTcGdjGJ GdYdGbI Hjf GdYeGd h GdOhdI h GdJfXje GdfbGHj aj Xd SjGSGJ GdJMQjQ GdGbJUGOj h cPG GhVGY GdYeGd aj eUQ Hjf YdGbGJ Yed LOjOI h JfXje fbGHj bOje h GdKGHJ h GdeJZjQ aj HfGA GdWHbI GdYGedI GdeUQjI h cPG eTcdGJ GdWHbI GdYGedI aj eUQ (B((3JMdjd GLJeGYj dBKGQ JWHjb SjGSGJ GdGUdGM GdGbJUGOj(B) (3h GNjQG GdKbGaI dOi HYV TQGFM GdWHbI GdYGedI(B.s
Keywords: (3GdJMhdGJ GdGLJeGYjIs; (3GdJMhdGJ GdGbJUGOjIs; (3GdJMhdGJ GdSjGSjIs; (3GdYeGds